Intellectuals don't need God and other modern myths : building bridges to faith through apologetics - McGrath, Alister Edgar, 1953- (Grand Rapids, MI : Zondervan, 1993)
Includes bibliographical references and index.
Originally published : Bridge building.--Leicerster, UK: IVP,1992
Keywords: Apologetics -- 20th century